The effect of self-compassion on the self-regulation of health behaviors: A systematic review. (December 2019) - Biber, David D; Ellis, Rebecca
The purpose of this review was to systematically review the published research on the effect of self-compassion interventions on health behaviors. A self-regulation intervention was defined as participants engaged in goal-setting behavior, goal-directed behavior, monitoring, and/or adjusting health behavior. Seven studies met the inclusion criteria and were analyzed in this review. Self-compassion interventions were just as effective as other behavior change techniques at improving self-regulation of health behavior. The review discusses sample characteristics, study design, health behavior measures, self-compassion intervention implementation, and the theoretical frameworks of the studies, along with limitations of the research and suggestions for future researchers.